Behavior of Piles subjected to Combined Axial and Lateral Loading - Al-Amery, Saja Saad; Al-Dahlaki, Mohammed Hussein (Engineering, Technology & Applied Science Research, 2025)
Pile foundations are employed to sustain both vertical and horizontal loads in various geotechnical applications, including coastal and offshore engineering. The contemporary design methodology analyzes the response of piles under combined horizontal and vertical loads independently and then superimposes them. This simple analytical method does not account for the combined loads' coupling effect. The number of studies on this subject is limited and the findings thus far are unclear about the effect of vertical loads on the lateral response of piles. In this paper, a number of model experiments were performed under different load conditions using the particle image velocimetry technique in well-graded sandy soil with a relative density of 65%. The results indicate that the presence of a low vertical load improves the lateral behavior of piles with L/D ratio (20, 25) due to the soil densification effect, and when the vertical load becomes 60 and 80% it results in a declining of the pile's lateral capacity. In piles with L/D ratio equal to 30, the P-∆ effect is more significant than the soil densification impact, which produces more pile deformation. This study also discusses the lateral displacement along the pile shaft using the PIV technique.